INTEGRAL DELTA DAN SIFAT-SIFATNYA - Talakua, Mozart W.; van Delsen, Marlon S. N. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2013)
Delta integral is the development of Riemann integral. The definition of Delta integral can be develop from definition of ï¤ -partition with construction and constructive definition of Riemann integral. A function f : ï›a,bïï‚®ïƒ‚ is said to be Riemann integralable on ï›a,bï , then it is also Delta integralable. But partition of Delta integral is refine from Riemann integral. So that the value of Delta integral function f on ï›a,bï is better with Riemann integral.